Socialization and Implementation of Digital Media in the Development of Promotional Videos for Guak Lago Camping Ground Tourism - Sayuti, Muhammad; Aggy Pramana Gusman; Okta Andrica Putra; Harkamsyah Andrianof; Hasri Awal; Melisa Suardi (Journal of Community Service and Application of Science, 2025)
Nestled in the heart of nature, Bumi Perkemahan Guak Lago holds extraordinary tourism potential, yet remains trapped in the shadow of obscurity. The subject of this community service is a hidden gem awaiting its moment in the spotlight, where promotion still relies on conventional methods with limited reach. The prevailing phenomenon is a paradox: a captivating landscape enjoyed only by a handful of local visitors, while a vast wave of digital tourists actively seeks new destinations that go viral on their screens. This Community Service (Pengabdian kepada Masyarakat/PKM) initiative acts as a bridge, shifting the paradigm by bringing the winds of digital change directly to the managing community. The applied method was a series of transformative interactions, beginning with intensive socialization on the importance of digital media, followed by practical training and direct mentoring in visual content production. This process went beyond mere theory, immersing participants in every stage—from capturing images with smartphones and basic editing to distribution strategies on social platforms. The overall outcome of this activity is commendable: the birth of a professional promotional video entirely crafted by the local community, which now serves not only as a promotional tool but also as a new symbol of pride and self-reliance. The activity successfully ignited the spark of digital literacy, transforming passivity into activity, turning mere site caretakers into confident content creators. Its impact flows like the waters of Guak Lago refreshing, bringing new life, and opening a stronger current of economic opportunities for sustainable village tourism. This empowerment is not an end but the first step on a long journey toward promotional self-sufficiency in the digital era.